3D Numerical Study and Parametric Analysis of PV/T Design Effect on Thermal and Electrical Performance - Souissi, Ahmed Saad Eddine; Masmali, Majed; Fterich, Mohamed; Touti, Ezzeddine; Chouikhi, Houssam (Engineering, Technology & Applied Science Research, 2024)
This paper explores the influence of design variations on the electrical and thermal efficiencies of PV/T (Photovoltaic-Thermal) systems. Utilizing COMSOL Multiphysics, three different PVT configurations with varying air duct designs were studied. The results demonstrated significant enhancements in both electrical and thermal efficiencies, with the PVT-3 configuration outperforming PVT-1 and PVT-2. Specifically, PVT-3, incorporating fin-shaped air ducts, exhibited the lowest recorded panel temperature of 55 °C, indicating improved electrical efficiency and thermal performance. Also, PVT-3 achieved the highest average thermal efficiency of 46.35% and the best electrical performance of 13.91%. Furthermore, the study highlights ameliorated airflow dynamics and uniformity within the ducts, particularly with the redesigned air inlet. These findings underscore the importance of design innovations in optimizing temperature management and energy output in PVT systems. It is worth noting that the tests were conducted under identical operating conditions, including air velocity, inlet temperature, ambient temperature, and solar irradiation.